Chest CT findings in COVID-19 - Radosław Serek; Małgorzata Serek (Wiedza Medyczna, 2021)
RT-PCR is the gold standard in the diagnosis of COVID-19 infections, due to its high specificity. However, there are clinical situations in which chest CT may prove vital, for example in patients with high clinical and epidemiologic suspicion towards COVID-19 before positive RT-PCR conversion or in detecting complications. Researchers have developed scales that, based on the findings in chest CT, help predict the severity of the disease.There are three main pathologic patterns of lung injury that correlate with the duration of COVID-19 symptoms. Epithelial pattern with diffuse alveolar damage and desquamation/reactive hyperplasia of pneumocytes; vascular pattern with capillary congestion and (micro)thrombi and fibrotic pattern with interstitial fibrous changes. The epithelial pattern and vascular pattern appear early, even before the symptoms of the disease, whereas the fibrous pattern appears approximately three weeks after the onset of the disease.Typical findings on chest CT in COVID-19 infection are: GGO, consolidation, GGO mixed with consolidation, interlobular septal thickening, air bronchogram sign, crazy paving, bronchial wall thickening and vascular enlargement.Findings that may suggest a different etiology include multiple nodules, tree-in-bud opacities, bronchiectasis, pleural and pericardial effusion, extensive consolidations.